Biological Aspects of Keperas Fish (Cyclocheilichthys apogon) in Batutegi reservoir, Tanggamus Regency, Lampung Province - Marson Marson; Taufik Hidayah (Universitas Muhammadiyah Palembang, 2021)
The research aims to analyze several biological aspects of the squeezed fish in Batutegi Lampung Reservoir. The study used an experimental method of capture used net capture tool with mesh-size 1.5-2.5 inches. Sample fish measured their total length, weighed in weight, and examined their stomachs to determine what type of food they had. We researched in February, August, and November 2017. The example of keperas fish caught amounted to 415 individuals. Analysis of long-weight relationships showed that February and August were allometrically negative, while November allometric was positive. The condition factor is worth one at each station and month. The eating habits of squeezed fish are plants 50%, fish 15%, insects 10%, worms 9%, phytoplankton 8%, and zooplankton 8%. The growth pattern of fish squeeze in November is isometric and allometric positive due to the development of gonads. The food habits of fish keperas are omnivorous, with the composition according to food availability in the environment.